The Correlation Analysis of Macronutrient Intake and Balanced Nutrition Index with the Degree of Depression in Preclinical Medical Students - Nina Indriyani Nasruddin; Edy Husnul Mujahid; Arimaswati; Sufiah Asri Mulyawati (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: Depression is a mood disorder characterised by deep feelings and a loss of interest in things you like. Many teenagers, including medical students worldwide, suffer from depression, a mental health problem. Depression affects the way the body processes food and can cause changes in metabolism. A decrease in leptin levels can accompany depression symptoms, leading to a decrease in appetite and influencing changes in nutritional status. Purpose(s): This study aims to analyse the relationship between macronutrient intake and the balanced nutritional index (BNI) on depressive symptoms in pre-clinical students at the Faculty of Medicine, Halu Oleo University. Method: This study used a cross-sectional design. The number of samples in this research was 96. We obtained the macronutrient intake using the 2x24-day Food Recall and the Balanced Nutrition Index (BNI), questionnaire to assess whether the consumed food was in accordance with dietary recommendations. We obtained depressive symptoms by completing the Beck Depression Inventory-II (BDI II) questionnaire. We then analysed the data using the rank-spearman test. Results: Of the samples, 21.9% had insufficient carbohydrate intake, 16.7% had insufficient fat intake, and 3.1% had insufficient protein intake. Of the 96 samples, there were 5 students who experienced severe depression (5.2%). There is a weak positive correlation between carbohydrate intake and depressive symptoms (p = 0.017, r = 0.244). There is no correlation between BNI and depressive symptoms in pre-clinical students at the Faculty of Medicine, Halu Oleo University. Conclusion: Macronutrient intake, especially carbohydrates, has a correlation with depressive symptoms in pre-clinical students at the Faculty of Medicine, Halu Oleo University. Keywords: BNI;Depressive Symptoms;Macronutriens; Medical Students